A probabilistic approach to identifying run scoring advantage in the order of playing cricket. Issue 4 (August 2021) - Samad, Manar D; Sen, Sumen
In the game of cricket, the decision to bat first after winning the toss is often taken to make the best use of superior pitch conditions and set a big target for the opponent. However, the opponent may fail to show their natural batting performance in the second innings due to several factors, including deteriorated pitch conditions and excessive pressure of chasing a high target score. The advantage of batting first has been highlighted in the literature and expert opinions. However, the effect of batting and bowling order on match outcome has not been investigated well enough to recommend an adjustment of potential bias. This study proposes a probability-based model to study venue-specific scoring and chasing characteristics of teams with different match outcomes. A total of 1117 one-day international cricket matches held in ten popular venues are analyzed to show substantially high scoring likelihood when the winning team bat in the first innings. In a high scoring match, results suggest that the same bat-first winning team is very unlikely to score or chase the same high score if they bat in the second innings. We use the Bayesian rule to identify the bias in the scoring likelihood due to the playing order (bat-first versus bat-second). The bias is adjusted by revising the second innings target in a way that equalizes winning and run scoring likelihoods of both teams. The data and source code have been shared publicly for future research in creating competitive match outcomes by eliminating the advantage of batting order in run scoring.